The complete mitochondrial genome of a striped sole Zebrias zebrinus (Pleuronectiformes: Soleidae). (December 2013) - Wang, Zhong-Ming; Shi, Wei; Jiang, Jin-Xia; Wang, Shu-Ying; Miao, Xian-Guang; Huang, Liang-Min; Kong, Xiao-Yu
<x xml:space="preserve">Abstract</x> Zebrias zebrinus belongs in the family Soleidae of Pleuronectiformes. There are overlaps in the ranges of identification characters between Z. zebrinus and another striped sole Z. fasciatus. In this study, the complete mitochondrial genome of Z. zebrinus was first determined. The total length was 16, 758 bp, including 13 protein-coding genes, 22 tRNA genes, and 2 rRNA genes (12S and 16S), as well as a putative control region and a putative L-strand replication origin (OL). Gene contents, locations, and arrangements were identical to those of typical bony fishes. The overall base composition of the mitogenome was 28.7%, 30.0%, 15.2%, and 26.1% for A, C, G, and T, respectively, with an A+T content of 54.8%. This result would expect the contribution to the molecular identification of this species and further phylogenetic study of Soleidae and Pleuronectiformes.